The Potential Therapeutic Effects of Artesunate on Stroke and Other Central Nervous System Diseases. (27th December 2016) - Zuo, Shilun; Li, Qiang; Liu, Xin; Feng, Hua; Chen, Yujie
Abstract : Artesunate is an important agent for cerebral malaria and all kinds of other severe malaria because it is highly efficient, lowly toxic, and well-tolerated. Loads of research pointed out that it had widespread pharmacological activities such as antiparasites, antitumor, anti-inflammation, antimicrobes activities. As we know, the occurrence and development of neurological disorders usually refer to intricate pathophysiologic mechanisms and multiple etiopathogenesis. Recent progress has also demonstrated that drugs with single mechanism and serious side-effects are not likely the candidates for treatment of the neurological disorders. Therefore, the pluripotent action of artesunate may result in it playing an important role in the prevention and treatment of these neurological disorders. This review provides an overview of primary pharmacological mechanism of artesunate and its potential therapeutic effects on neurological disorders. Meanwhile, we also briefly summarize the primary mechanisms of artemisinin and its derivatives. We hope that, with the evidence presented in this review, the effect of artesunate in prevention and curing for neurological disorders can be further explored and studied in the foreseeable future.